The abundance and species richness of the spiders (Araneae : Arachnida) associated with a rivine and sweet thorn thicket, rocky outcrop and Aloe Marlothii thicket in the Polokwane Nature Reserve, Limpopo Province - Khoza, Thembile Tracy (University of Limpopo (Turfloop Campus), 2008)
Refer to document
Thesis (MSc. (Zoology)) --University of Limpopo, 2008
Keywords: Spiders; Rivine thorn thicket; Sweet thorn thicket; Rocky outcrop; Aloe Marlothii thicket; 595.44; Spiders -- South Africa; Arachnida -- South Africa